Gratitude training to improve quality of life for schizophrenic family caregivers - Farra Anisa Rahmania; Rumiani Rumiani (Jurnal Ilmiah Psikologi Terapan, 2022)
This study aims to determine the effect of gratitude training on the quality of life of schizophrenic family caregivers. The design in this study used two groups of pretest-post test with follow-up. The participants in this study were 10 schizophrenic family caregivers aged by 19-60 years. The number of participants in this study was 5 participants in the experimental group with 4 female participants and 1 male participant (M age = 41.2 years) and 5 participants in the control group with 4 female participants and 1 male participant (M age = 46.4 years). This study used the quality of life scale (WHOQOL-BREF) developed by the World Health Organization with Cronbach’s alpha reliability score of .828. The data analysis in this study used anava mixed. The results of the analysis showed that the research data was significant at p = .009 (p < .05) with a partial eta squared value of .553. The results showed that gratitude training 55.3% affected improving the quality of life of schizophrenic family caregivers. This intervention could be applied to increasing the family caregiver’s quality of life in the future.